Structural properties of (B3) TlP under pressure - Daoud, Salah; Bioud, Nadhira (International Journal of Physical Research, 2014)
We present an Ab-initio study of the pressure effect on the structural properties of thallium phosphide (TlP) compound. The plane-wave pseudopotential approach to the density functional theory (DFT) within the local density approximation (LDA) implemented in Abinit code was used. The equilibrium lattice parameter, bulk modulus and its pressure derivatives, crystal density, near-neighbor and nearest-neighbor distances are calculated. The threshold pressure of the phase transition, the volume collapses and the Debye temperature are also obtained. Our results are in general in very good agreement with the previous results of the literature. Keywords: PP-PW Approach, Structural Properties, TlP Compound.